Biological Effects of Space Hypomagnetic Environment on Circadian Rhythm - Xue, Xunwen; Ali, Yasser F.; Luo, Wanrong; Liu, Caorui; Zhou, Guangming; Liu, Ning-Ang (Frontiers in Physiology, 2021)
The intrinsic earth magnetic field (geomagnetic field, GMF) provides an essential environmental condition for most living organisms to adapt the solar cycle by rhythmically synchronizing physiological and behavioral processes. However, hypomagnetic field (HMF) of outer space, the Moon, and the Mars differs much from GMF, which poses a critical problem to astronauts during long-term interplanetary missions. Multiple experimental works have been devoted to the HMF effects on circadian rhythm and found that HMF perturbs circadian rhythms and profoundly contributes to health problems such as sleep disorders, altered metabolic as well as neurological diseases. By systemizing the latest progress on interdisciplinary cooperation between magnetobiology and chronobiology, this review sheds light on the health effects of HMF on circadian rhythms by elaborating the underlying circadian clock machinery and molecular processes.